Kontribusi Perbankan Syariah terhadap Permodalan UMKM Selama Pandemi Covid-19 - Ana Zahrotun Nihayah; Lathif Hanafir Rifqi (Jurnal Ecodemica : Jurnal Ekonomi Manajemen dan Bisnis, 2022)
Islamic banks as one of the MSME stakeholders, must participate in helping and resurrecting MSMEs so that they can grow and develop like their normal conditions. This research uses a descriptive approach by using secondary data from Islamic banking statistics during the COVID-19 period (March 2020 to February 2022). Data analysis used reduction, display, and descriptive analysis techniques. The results showed that the role of Islamic banks during the COVID-19 pandemic was manifested in three ways, namely 1) as a distributor of assistance from the government, 2) providing financing restructuring, and 3) encouraging increased financing for MSMEs. The development of Islamic bank financing during the COVID-19 pandemic was relatively stable and even had an average increase compared to the pre-covid-19 period. The increase in working capital financing was by 21%, while the average investment financing increased by 31.72%. The NPF ratio of Islamic banks during the COVID-19 pandemic on a monthly average was above the maximum standard set by Bank Indonesia for this type of working capital financing, which was 5.05%. On the other hand, the NPF ratio of working capital financing above 5% also occurred 15 times in 24 months of observation. Meanwhile, the NPF ratio for investment financing during the COVID-19 period was, on average, below Bank Indonesia's standard of 4.05%. However, in certain months it shows that the NPF ratio for investment financing is still above 5%. This must be a concern because Islamic banks are considered not to apply the principle of prudence in providing financing. Keywords: Covid-19, Islamic Banks, Productive Financing, Capital, SMEs